Novel one-step lignin microsphere preparation for oral tissue regeneration applications - Shi, Anyuan; Guo, Li; Gu, Chunning; Zhan, Yunni; Zhou, Xuelian; Cheng, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
Lignin is a naturally derived biomacromolecule with excellent biocompatibility and the potential for biomedical application. For the first time, this study isolated nanosized lignin microspheres (LMSs) directly from wheat straw with a polyol-based deep eutectic solvent. The size of these LMSs can be regulated by changing the isolation parameters, ranging from 90 nm to 330 nm. The structures of these LMSs were comprehensively investigated by SEM, gel permeation chromatography (GPC), HSQC NMR, and 31P NMR, which explained the formation mechanism of the hydrophobicity-induced self-assembly. The LMSs show good antioxidation of 52.99%–76.26% toward DPPH. In vitro biomedical tests further revealed that the LMSs at concentrations <25 μg/mL had good biocompatibility toward gingival mesenchymal stem cells (GMSCs) and jaw bone marrow mesenchymal stem cells (JBMMSCs), with a low apoptosis rate, outperforming other lignin materials. The presented results highlighted the application of the nanosized LMSs as a potential biomaterial in oral tissue regeneration.